2021
DOI: 10.1177/0363546520984122
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid Receptor Agonists Suppress Muscle Fatty Infiltration in Mice

Abstract: Background: The infiltration of fat tissue into skeletal muscle, a condition referred to as muscle fatty infiltration or fatty degeneration, is regarded as an irreversible event that significantly compromises the motor function of skeletal muscle. Purpose: To investigate the effect of retinoic acid receptor (RAR) agonists in suppressing the adipogenic differentiation of fibroadipogenic progenitors (FAPs) in vitro and fatty infiltration after rotator cuff tear in mice. Study Design: Controlled laboratory study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Conversely, RA treatment in a RARdeficient/inactivated system sustains FAP fibrogenesis [69]. In parallel, treatment with RAR-agonists during chronic injury increased the expression of collagen genes while no fibrotic infiltrations were histologically evident [125]. Important evidence impacting on the putative clinical use of RAR agonists was found in a mouse model of fibrodysplasia ossificans progressiva (FOP) where palovarotene was found to limit FAPmediated skeletal muscle ossification albeit with high toxicity upon chronic administration [127].…”
Section: Retinoic Acid Signalingmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, RA treatment in a RARdeficient/inactivated system sustains FAP fibrogenesis [69]. In parallel, treatment with RAR-agonists during chronic injury increased the expression of collagen genes while no fibrotic infiltrations were histologically evident [125]. Important evidence impacting on the putative clinical use of RAR agonists was found in a mouse model of fibrodysplasia ossificans progressiva (FOP) where palovarotene was found to limit FAPmediated skeletal muscle ossification albeit with high toxicity upon chronic administration [127].…”
Section: Retinoic Acid Signalingmentioning
confidence: 99%
“…In FAPs, imatinib prevents the expression of Accepted Article fibrogenic genes following PDGF-AA stimulation [149]. Intriguingly, imatinib also inhibits IMAT development in rotator cuff tear mouse model [125], implying that PDGFR signaling may crosstalk with other proadipogenic pathways. Similar to imatinib, nilotinib and crenolanib also reduce fibrosis in mdx mice [34,148].…”
Section: Platelet-derived Growth Factor Receptor-alpha (Pdgfr) More Than a Mere Surface Markermentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, four studies 19,[24][25][26] investigated the mechanism of fatty degeneration based on the effects of inhibitor and ligand administration.…”
Section: A Systematic Review Of the Rst Evaluationmentioning
confidence: 99%
“…Both the number of FAPs and the adipogenic differentiation potential of FAPs increased in large sizes of RCT [ 8 ]. Furthermore, previous studies also reported that PDGFRα pathways inhibitor imatinib [ 1 ], retinoic receptors agonist adapalene [ 9 ], and β-3 agonist amibegron [ 10 ] could suppress adipogenic differentiation of FAPs and mitigate fatty infiltration in RCT. Thus, FAPs significantly contribute to ectopic fatty formation in rotator cuff muscles, and it is a promising strategy to ameliorate excessive fatty infiltration by targeting FAPs after RCT.…”
Section: Introductionmentioning
confidence: 99%